“Их цааз”-ын эх бичгийн судалгааны зарим асуудал - Б.Батбаяр (Acta Mongolica, 2007)
This article deals with the urgent textological problems of the "Ikh tsaaz" (Great Law) adopted in the year of 1640, concerning its original text and the name, the authors and those who ratified it, the date and the place of compiling, the sources used in it and so on.